Deconstructing Junior High School English Learning Materials based on Microlearning - Nugrahani, Riemas Dina; Dewanti, Ratna; Iskandar, Ifan; Maharani, Suci (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2023)
Microlearning provides smaller units of a subject adapted using technologies that can be accessed anywhere in a relatively short period, making learning activities more efficient and helping students learn with a specific focus in a brief session. This study aims to analyze the extent of microlearning in the existing junior high school English learning materials and describe the description of junior high school English learning materials based on microlearning. This study uses a qualitative research approach to analyze 25 English learning materials applied and used by junior high school English language teachers in East Jakarta, DKI Jakarta. The study found that most of the junior high school English learning materials are not microlearning-based as they do not fulfill the indicators of microlearning-based English materials for the junior high school level. The procedure of deconstructing 36 basic competencies into microlearning object material includes recognizing the topic and the instructional activities as well as finding suitable micro-learning object materials for the activities. The total 195 microlearning object materials are varied, such as Short videos, Games, PPTs, Quizizz, Interactive e-learning Websites, podcasts, YouTube videos, digital flashcards, and many more. In summary, as the existing English learning materials do not fulfill the indicators, the procedure of deconstructing basic competencies is made to form micro-learning object materials.